EDUKASI PERENCANAAN KEUANGAN DAN PENGELOLAAN UANG SAKU BAGI KARANG TARUNA DI KELURAHAN DURI KOSAMBI - Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2024)
This community service activity aims to increase the understanding of Karang Taruna members in Duri Kosambi Village regarding the importance of financial planning and wise management of pocket money. Problems often faced by teenagers and young people are consumptive behavior and a lack of ability to manage expenses according to priority needs. This activity was carried out through lectures and question-and-answer discussions, providing material on financial literacy, simple budgeting, pocket money management, and the importance of saving from an early age. The results of the activity showed an increase in participants' understanding of personal financial management and awareness to be more disciplined in using pocket money. This education is expected to shape healthy financial behavior so that Karang Taruna members can become an independent and economically responsible young generation.